(untitled) - Bergdahl, Michael (Hoboken, N.J., 2004)
Michael Bergdahl, author of What I Learned From Sam Walton: How to Compete and Thrive in a Wal-Mart World, points out the benefits of such meetings, where everyone has to pay for their own coffee and donuts at an honor bar. Every manager hears the same message in the same way. Ideas, successes and failures are shared. Strategic execution can begin while competitors are playing golf.
Keywords: Retail trade,Industrial management,Thương mại bán lẻ,Quản lý công nghiệp; Management,Quản lý